2018
DOI: 10.2147/ott.s154754
|View full text |Cite
|
Sign up to set email alerts
|

CDCA5 regulates proliferation in hepatocellular carcinoma and has potential as a negative prognostic marker

Abstract: BackgroundCDCA5 plays an important role in the development of various human cancers, but the associated mechanisms have not been investigated in hepatocellular carcinoma (HCC).Materials and methodsWe evaluated expression levels and functions of CDCA5 in HCC and showed that CDCA5 is upregulated in HCC tissues compared with paired or unpaired normal liver tissues.ResultsIncreased CDCA5 expression in HCCs was significantly associated with shorter survival of patients. Knockdown of CDCA5 using lentivirus-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
42
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 31 publications
7
42
1
Order By: Relevance
“…The results showed that the OS probability of patients with high expression of CDCA5 and CDCA8 in tumor tissues was significantly decreased. This was consistent with the effect of the two on the survival time of patients in other types of tumors [30][31][32]. Secondly, we analyzed the correlation between the two and all genes involved in the p53 signaling pathway.…”
Section: Discussionsupporting
confidence: 77%
“…The results showed that the OS probability of patients with high expression of CDCA5 and CDCA8 in tumor tissues was significantly decreased. This was consistent with the effect of the two on the survival time of patients in other types of tumors [30][31][32]. Secondly, we analyzed the correlation between the two and all genes involved in the p53 signaling pathway.…”
Section: Discussionsupporting
confidence: 77%
“…Interestingly, USP22 levels are significantly upregulated in human brain glioma cells, and it is associated with cell regulatory protein Cyclin B1 expression [22]. Cyclin B1 plays an important role in cell cycle arrest at the G2/M phase and serves a crucial role in the expansion of tumor cells in HCC [23]. Our results demonstrated that Cyclin B1 expression was decreased in the combined group.…”
Section: Discussionmentioning
confidence: 60%
“…Two of the genes in our biomarker panel i.e. CDCA5 and RAMP3 already identified as prognostic markers in HCC in literature [58,59]. In recent past, role of pseudogenes has been revealed in pathogenesis of cancer [6062] including HCC (25391452, 28823960).…”
Section: Conclusion and Discussionmentioning
confidence: 99%